Implementing the Client Protection Principles : A Technical Guide for Investors - Forster, Sarah Jacqueline; Lahaye, Estelle Marie; Clark, Heather Anne; Koning, Antonique M.; McKee, Kate (World Bank, Washington, DC, 2015)
This guide continues to be a ‘living’ document that will be updated as practice evolves. Investors are strongly encouraged to provide feedback on how to improve this guide and to share additional material that could be included. The Guide is organized as follows: section two describes the principles and their importance to ensuring sustainable microfinance development that serves the best interests of clients. Section three provides an update on the smart campaign. Section four offers practical advice on approaches and tools to incorporate the principles into investment processes. Section five highlights questions that investment organizations are facing and emerging responses. Finally, section six provides a list of resources and tools.